2016
DOI: 10.3233/nre-151292
|View full text |Cite
|
Sign up to set email alerts
|

Transvertebral direct current stimulation paired with locomotor training in chronic spinal cord injury: A case study

Abstract: This publication was supported by the National Center for Research Resources and the National Center for Advancing Translational Sciences, National Institutes of Health, through Grant UL1TR000117, and the HealthSouth Cardinal Hill Stroke and Spinal Cord Endowment (1215375670).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Trans-spinal direct current stimulation (tsDCS) is a new neuromodulatory technique utilizing polarization phenomena. Despite numerous unknowns with respect to physiological mechanisms and neuronal interactions within spinal networks, tsDCS has been increasingly used over recent years in the rehabilitation of patients following neurological injuries (23,40,49) or as an addition to physical training in sport (8,13). To date, it has been shown in both animals and humans that trans-spinally applied constant current can modify the effectiveness of synaptic actions of descending pathways (1, 2), ascending tracts (52,53), or local interneuronal circuits (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Trans-spinal direct current stimulation (tsDCS) is a new neuromodulatory technique utilizing polarization phenomena. Despite numerous unknowns with respect to physiological mechanisms and neuronal interactions within spinal networks, tsDCS has been increasingly used over recent years in the rehabilitation of patients following neurological injuries (23,40,49) or as an addition to physical training in sport (8,13). To date, it has been shown in both animals and humans that trans-spinally applied constant current can modify the effectiveness of synaptic actions of descending pathways (1, 2), ascending tracts (52,53), or local interneuronal circuits (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, studies have aimed at developing transcutaneous spinal direct current stimulation (tsDCS) as a non-invasive technique to modulate spinal cord function in humans. Most of these studies have focused on the after-effects of tsDCS on motor-related functions (Cogiamanian et al , 2011; Lim & Shin, 2011; Lamy et al , 2012; Hubli et al , 2013; Bocci et al , 2014; Knikou et al , 2015; Perrotta et al , 2016; Donges et al , 2017; Winkler et al , 2010; Powell et al , 2016). In contrast, although invasive electrical stimulation of the spinal cord (SCS) using epidural electrodes is extensively used as a mean to reduce pain in patients with chronic neuropathic radicular pain (Nizard et al , 2012; Deer et al , 2014), very few experiments have been conducted to assess the possible effects of tsDCS on the spinal transmission and processing of nociceptive inputs.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also demonstrated that tsDCS can enhance functional aspects of behaviors such as walking, breathing, and muscle tone. In a recent case study, 24 sessions of cathodal tsDCS combined with robotic locomotor training were found to improve functional outcomes compared with sham treatment sessions for a patient with spinal cord injury (57). Moreover, transcranial DCS has been shown to enhance cognitive and motor functions in healthy individuals, as well as in individuals affected by stroke, psychiatric disorders, or Parkinson's disease (32,39,68).…”
mentioning
confidence: 99%